2020
DOI: 10.1038/s41416-020-01102-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinically and biologically relevant subgroups of Wilms tumour defined by genomic and epigenomic analyses

Abstract: Background Although cure rates for Wilms tumours (WT) are high, many patients receive therapy with attendant long-term complications. Our goal was to stratify WT using genome-wide analyses to identify candidate molecular features for patients who would benefit from a reduction in therapy. Methods We generated DNA methylation and exome sequencing data on WT–kidney pairs (n = 57) and unpaired tumours (n = 27) collected either at our centre or by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…HOXA5 is a tumor suppressor gene dysregulated in expression and methylation in several types of cancer [ 39 ]. Our DNAm studies in Wilms tumor tissues identified hypermethylation of HOXA5 CpG sites [ 40 , 41 ]. This finding is of interest since BOS individuals appear to have an increased risk for Wilms tumor [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOXA5 is a tumor suppressor gene dysregulated in expression and methylation in several types of cancer [ 39 ]. Our DNAm studies in Wilms tumor tissues identified hypermethylation of HOXA5 CpG sites [ 40 , 41 ]. This finding is of interest since BOS individuals appear to have an increased risk for Wilms tumor [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brzezinski et al observed that TRIM28‐ mutated tumours belong to a subgroup of WT with genome‐wide dysregulation of DNA methylation [22] and display a very distinct and recognizable DNA methylation pattern (Brzezinski, personal communication).…”
Section: Trim28 Variants In Patients With Wtmentioning
confidence: 99%
“…Additionally, global hypomethylation of TEs has been associated with genomic instability in various adult cancer types [51]. Although WTs generally harbour few mutations or copy number changes compared with adult cancer, TRIM28‐ mutated WTs were recently shown to be part of a subgroup of WTs which are less stable genomically [22].…”
Section: Biological Functions Of Trim28mentioning
confidence: 99%
“…Moreover, patients who present with the genome-wide dysregulation of DNA methylation have been associated with high-risk histology tumors and the occurrence of relapse (Foster et al, 2021), indicating that abnormal DNA methylation, either alone or in combination with the existing surveillance methods, may serve as a potential epigenetic biomarker or therapeutic target for WT patients. Currently, CpG sites that have been shown to be associated with potential WT pathogenesis include Wilms tumor 1 (WT1) (Brzezinski et al, 2021), WTX (Pelletier et al, 1991), TP53 (Rivera et al, 2007), and 11p15 (Andrade et al, 2014), and the methylation of some of these genes can be detected in peripheral blood (Fiala et al, 2020). In recent studies, methylation patterns have been studied and recommended as a potential method for disease classification and prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, DNA methylation has been demonstrated to be involved in the pathogenesis of many diseases, including tumor development. Previous studies have shown that genome-wide dysregulation of DNA methylation is associated with WT patients who display high-risk histology (Brzezinski et al, 2021). The early and prevalent events in WT are associated with DNA methylation changes affected many common cellular functions, most of which are involved in the epigenetic regulation of early renal development or transcription.…”
Section: Introductionmentioning
confidence: 99%